Aeromagnetic signature of the geology and mineral resources near the Pebble porphyry Cu-Au-Mo deposit, southwest Alaska - Anderson, Eric D. (Colorado School of Mines. Arthur Lakes Library, 2007)
2013 Fall. Includes illustrations (some color), maps (some color). Includes bibliographical references. Aeromagnetic data are used to better understand the geology and mineral resources near the Late Cretaceous Pebble porphyry Cu-Au-Mo deposit in southwestern Alaska. The reduced-to-pole (RTP) transformation of regional-scale aeromagnetic data show that the Pebble deposit is within a cluster of magnetic anomaly highs. Similar to Pebble, the Iliamna, Kijik, and Neacola porphyry copper occurrences are in magnetic highs that trend northeast along the crustal-scale Lake Clark fault. A high-amplitude, short- to moderate-wavelength anomaly is centered over the Kemuk occurrence, an Alaska-type ultramafic complex. Similar anomalies are found west and north of Kemuk. A moderate-amplitude, moderate-wavelength magnetic low surrounded by a moderate-amplitude, short-wavelength magnetic high is associated with the gold-bearing Shotgun intrusive complex. The RTP transformation of the district-scale aeromagnetic data acquired over Pebble permits differentiation of a variety of Jurassic to Tertiary magmatic rock suites. Jura-Cretaceous basalt and gabbro units and Late Cretaceous biotite pyroxenite and granodiorite rocks produce magnetic highs. Tertiary basalt units also produce magnetic highs, but appear to be volumetrically minor. Eocene monzonite units have associated magnetic lows. The RTP data do not suggest a magnetite-rich hydrothermal system at the Pebble deposit. The 10 km upward continuation transformation of the regional-scale data shows a linear northeast trend of magnetic anomaly highs. These anomalies are spatially correlated with Late Cretaceous igneous rocks and in the Pebble district are centered over the granodiorite rocks genetically related to porphyry copper systems. The spacing of these anomalies is similar to patterns shown by the numerous porphyry copper deposits in northern Chile. These anomalies are interpreted to reflect a Late Cretaceous magmatic arc that is favorable for additional discoveries of Late Cretaceous porphyry copper systems in southwestern Alaska. Aeromagnetic data help to understand the three-dimensional distribution of plutonic rocks near the Pebble porphyry copper deposit. Magnetic susceptibility measurements show that rocks in the Pebble district are more magnetic than rocks of comparable compositions in the Pike Creek-Stuyahok Hills volcano-plutonic complex. The reduced-to-pole transformation of the aeromagnetic data demonstrates that the older rocks in the Pebble district produce strong magnetic anomaly highs. The tilt derivative transformation highlights a strong, northeast-trending structural grain attributed to Tertiary volcanic rocks. Multiscale edge detection maps near-surface magnetic sources that are mostly outward dipping and coalesce at depth in the Pebble district. The total horizontal gradient of the 10 km upward continued magnetic data map a circular, deep magnetic contact along which the porphyry deposits occur. Forward and inverse magnetic modeling show that the magnetic rocks in the Pebble district extend to depths greater than 9 km. The magnetic inversion is constrained by a near-surface, three-dimensional geologic model that is attributed with measured magnetic susceptibilities from various rock types in the region. The inversion results indicate that several near-surface magnetic features with moderate susceptibilities converge with depth into magnetic bodies with higher susceptibilities. This deep magnetic source appears to rise towards the surface in several areas. An isosurface value of 0.02 SI is used to depict the magnetic contact between outcropping granodiorite and non-magnetic sedimentary host rocks. The contact is shown to be outward dipping. At depths around 5 km nearly the entire model exceeds the isosurface value indicating the limits of non-magnetic host material. The inversion results show the presence of a relatively deep, northeast trending magnetic low that parallels lineaments mapped by the tilt derivative. This deep low represents a strand of the Lake Clark fault. The geodynamic setting of an accreted island-arc terrane represent a region in which several types of mineral resources may occur. The mineral resources from southwest Alaska are classified into greenstone-hosted, oxidized intrusion-related, reduced intrusion-related, and epithermal. Aeromagnetic data are related to the classified mineral resource and outcropping geology to better understand the distribution of gold-rich mineral resources. Three magnetic domains are defined by the reduced-to-pole, upward continue, and tilt derivative transforms. The greenstone-hosted mineral resources that include VMS are mapped along magnetic lineaments mostly landward of the accreted island-arc. The oxidized intrusion-related mineral resources that include porphyry copper, skarn, and Alaska-type ultramafic-mafic complexes occur along magnetic anomaly highs in the Peninsular and Kahiltna domains. Characteristic short wavelength, high amplitude magnetic anomalies suggest additional Alaska-type ultramafic-mafic complexes and skarn resources in the Kahiltna and Kuskokwim domain. Magnetic depth estimates indicate potential greenstone-hosted and oxidized intrusion-related resources occur beneath 100 m of glacial deposits. Reduced intrusion-related resources are best imaged in the more landward, Kuskokwim magnetic domain. Epithermal resources are not well imaged. The mineral potential map highlights areas most favorable for additional mineral resources.